Avaliação do efeito da terapia sistêmica crônica com ácido zoledrônico na periodontite apical experimental em ratos - Nascimento, Isabelly Vidal do (2022)
Bisphosphonates (BFs) are drugs with direct action on bone tissue and its cells. Apical periodontitis is one of the most prevalent diseases and is characterized by an inflamed response to harmful stimuli that lead to the progressive loss of perradicular structures. Currently, very few studies seek to investigate the relationship between the systemic use of BP in AP. Therefore, the aim of this study was to evaluate the development of apical periodontitis in rats treated systemically with zoledronic acid (AZ). 128 male Wistar rats (Rattus novergicus) were randomly divided into two groups: a group treated with zoledronic acid (0.2mg/kg/week) and a control group that was administered saline solution (0.1ml/kg/week), Both intravenously, for 3 consecutive weeks, one month after the last dose, the AP was performed, the following week, animals were then dosed one dose and additionally they will be euthanized according to each evaluation period (7, 14, 21 and 28 days). Bone mandibles were evaluated for pulp necrosis, resorption, osteonecrosis, histomorphometric (polymorphonuclear, mononuclear, empty osteocyte lacunae and osteoclast count), immunohistochemistry (Active Kappa Nuclear Factor Receptor Ligand [RANK], osteoprotegerin [OPG], Nuclear factor-κB [NFkB] and Tumor necrosis factor-alpha [TNF-α]) and scanning electron microscopy associated with energy dispersive spectrometer (EDS) for quantification of the elements nitrogen, carbon, oxygen, calcium and phosphorus. A significance level of 95% (p<0.05) was considered. Treatment with accessible height distance significantly reduced bone resorption in the apically region of endodontically accessed teeth, both in terms of height, after 14 (p=0.0195), 21 (p=0.0003) and 28 days (p =0.0003), as in 14 (p=0.0002), 21 (p=0.0004) and 28 days (p=0.0007) and depth after 14 (p=0.0009), 21 (p =0.0020) and 28 days (p=0.0003). Regarding the apical lesion on the accessed side, the saline group presented an area that the AZ group on days 14 (p=0.0058), 21 (p=0.0004) and 28 (p=0.0003). Histologically, on the accessed side, after 21 (p=0.0278) and 28 days (p=0.0163) of endodontic access, the saline group showed a significant increase compared to the AZ in relation to the area of the apical lesion. Regarding PMN count, there was a significant increase after 21 (p=0.0343) and 28 (p=0.027) days in the AZ group compared to saline. The MN count showed a significant difference between the saline and AZ groups only on day 14 (p=0.0137). Regarding OPG immunoexpression, it was increased after seven (p<0.0001), 14 (p=0.0018), 21 (p=0.0004) and 28 (p=0.0004) days in the AZ group. RANKL immunoexpression showed a significant difference after 14 (p=0.0001), 21 (p=0.0175) and 28 (p<0.0001) days it was higher in the saline group than in the AZ group. NFkB p65 counts of (p=0.05) and TNF-α (p=0.0373) saw an increase in the AZ group after 28 days. In the qualitative analysis by SEM and EDS, treatment with AZ alters structural aspects due to the presence of micro cracks and changes in calcium and phosphorus levels in the apical regions of endodontically accessed teeth. AZ was found to modify the development of experimentally induced periodontitis at a projected, greater value than increased resorption. These processes also led to an exacerbation of the acute inflammatory, as well as an increase in the levels of OPG, NFkB and TNF-α, in addition to an elevation in the levels of RANKL.